INSIGHTS GAINED FROM THE SEISMICITY AROUND THE ZIPINGPU RESERVOIR BEFORE THE WENCHUAN MS8.0 EARTHQUAKE - Liu Yuanzheng; Ma Jin; Jiang Tong (Геодинамика и тектонофизика)
The 2008 Wenchuan MS8.0 earthquake occurred on Longmenshan fault zone (LMSF), which is at the eastern margin of the Tibetan plateau. The epicenter is near the Shuimogou earthquake swarm, which was thought to be triggered by the Zipingpu reservoir after its impounding in 2004. People have speculated that the large earthquake was triggered by the water filling of the reservoir. To figure out the role of the Zipingpu reservoir on the earthquake, the local seismicity recorded by the Zipingpu local seismic network during the period from 31 July 2004 to 11 May 2008 were analyzed in detail. The distribution of hypocenters showed that most earthquakes occurred on Yingxiu-Beichuan fault (YBF) in the reservoir area with hypocenters depth less than 10 km, which is a major source fault of the Wenchuan earthquake. Useful information on fault geometry in the depth was also obtained. The spatial-temporal distribution of hypocenters demonstrated clear migration pattern that indicated pore-pressure diffusion, it also showed a hydraulic diffusivity (D) of 0.7 m2/s. Previous experiments show the existence of the synergism process of the fault under a meta-instability state before fault sliding. It enhances the stress on the stronger portion of the fault and the synergism degree by reducing strength of the weak portions and by increasing the total length of weak portions. According to this view, the pore pressure diffusion by water filling of Zipingpu reservoir increased the total length of weak portions and enhanced the stress at the focal.